Compilation of Islamic Law as Judge's Consideration at a Religious Court in North Sulawesi, Indonesia - Bilalu, Naskur; Jamal, Ridwan; Harun, Nurlaila; Subeitan, Syahrul Mubarak (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
This study examines the Compilation of Islamic Law (KHI) as a consideration for Religious Court Judges in North Sulawesi in resolving legal cases. This paper is empirical legal research using the sociology of law approach based on facts related to the considerations of judges and decisions of the religious courts in North Sulawesi as the application of the Compilation of Islamic Law. The data collection technique is based on literature review, especially court decisions and in-depth interviews with judges. The findings show that there are four forms of application of KHI, namely: First, KHI is the main reference with considerations: 1) if there is no basis for legal considerations in Laws and Government Regulations; 2) KHI is the agreement of the ulema and is a series of written laws; 3) KHI is jurisprudence, Second, KHI is a reinforcement reference to Government Laws and Regulations with the following considerations: 1) KHI is a reaffirmation of Government Laws and Regulations; 2) KHI provides Islamic characteristics and values; 3) KHI is a special provision for Muslims; 4) KHI realizes marriages must be carried out based on the provisions of the law of religion and belief. Third, KHI is a special reference with the considerations: 1) KHI regulates specifically, while it is not found in laws and Government Regulations; 2) KHI is a special reference for Religious Courts; 3) KHI has regulated while the laws and regulations have not regulated, and Fourth, KHI is not a reference at all with the consideration that no legal basis is found.